Zyxin is involved in regulation of mechanotransduction in arteriole smooth muscle cells - Sun, Zhe; Huang, Shaoxing; Li, Zhaohui; Meininger, Gerald A. (Frontiers in Physiology, 2012)
Zyxin is a focal adhesion protein that has been implicated in the modulation of cell adhesion and motility, and is hypothesized to be a mechano-sensor in integrin-mediated responses to mechanical force. To test the functional role of zyxin in the mechanotransduction of microvascular smooth muscle cells (VSMC), we utilized atomic force microscopy (AFM) to apply localized pulling forces to VSMC through a fibronectin (FN) focal adhesion induced by a FN-coated bead on cell surface. Application of force with the AFM induced an increase of zyxin accumulation at the site of the FN-bead focal adhesion that accompanied the VSMC contractile response. Whereas, reduction of zyxin expression by using a zyxin-shRNA construct abolished the VSMC contractile response to AFM pulling forces, even though the zyxin-silenced VSMCs displayed increased adhesion to FN in both AFM adhesion assays and cell adhesion assays. The reduced zyxin expression significantly impaired cell spreading and reorganization of the actin cytoskeleton that could indicate a possible underlying reason for the loss of a contractile response to mechanical force. Consistent with these observations, zyxin silencing also resulted in reduced expression of Rac1, which plays an important role in the actin reorganization in VSMC, but increased TRIP6 and FAK expression, the latter being a major protein that promote cell adhesion. In conclusion, these data support an important enabling role for zyxin in VSMCs ability to mechanically respond to applied force.